Magnetostatic spin wave resonance in square-patterned Ni0.77Fe0.16Cu0.05Cr0.02 (Mu-metal) thinfilms - DEĞER, CANER (ELSEVIER SCIENCE BV, 2016)
Behavior of spin waves was investigated in patterned Mu-metal thin film both theoretically and experimentally. The Mu-metal(111) thinfilms with 7 nm thickness were grown by thermal evaporation technique in high vacuum condition. X-ray diffraction measurements showed that the film has a highly FCC crystalline structure. Saturation magnetization and coercive field values of sample obtained from vibrating sample magnetometer are around 500 emu/cm(3) and 10 Oe respectively at room temperature. The patterns were square shaped and size of squares were changed between 40-80 mu m. Theoretical model and computer program were developed for analyzing the FMR spectra. There is no magnetic anisotropy for in-plane and out-of-plane geometry by both theoretical and experimental investigations. Magnetostatic modes were observed for out-of-plane geometry and these modes were highly compatible with outputs of simulation model. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Square patterned thinfilm; Magnetostatic spinwave; Mu-metal; Ferromagnetic resonance; FERROMAGNETIC-RESONANCE; THIN-FILMS; ANISOTROPY; NIFE